Qualitative inquiry with persons with obesity about weight management in primary care and referrals - Bailey-Davis, Lisa; Pinto, Angela Marinilli; Hanna, David J.; Cardel, Michelle I.; Rethorst, Chad D.; Matta, Kelsey; Still, Christopher D.; Foster, Gary D. (Frontiers in Public Health, 2023)
Referrals to evidence-based weight management in the community-commercial sector are aligned with clinical recommendations but underutilized. This qualitative study explored patients' perceptions and expectations about obesity treatment in primary care and referral to community-commercial sector programs. Individual semi-structured interviews were conducted with a sample of US persons with obesity via telephone. Audiotape transcripts, interviewer notes, and independent review of data by two investigators allowed for data and investigator triangulation. Transcripts were analyzed using thematic analysis. Data saturation was reached with 30 participants who had a mean age of 41.6 years (SD 9.4), 37% male, 20% Black/African American and 17% Hispanic, 57% college educated, and 50% were employed full-time. Three primary themes emerged: 1) frustration with weight management in primary care; 2) patients expect providers to be better informed of and offer treatment options; and 3) opportunities and challenges with referrals to community-commercial programs. Patients expect that providers offer personalized treatment options and referrals to effective community-commercial programs are an acceptable option. If patient-level data are shared between clinical and community entities to facilitate referrals, then privacy and security issues need attention. Future research is needed to determine feasibility of implementing clinical to community-commercial referrals for obesity treatment in the US.